2022
DOI: 10.3389/frans.2022.930480
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Illicit Drug Use Trends During the Carnival Holiday in the Brazilian Capital Through Wastewater Analysis

Abstract: Cocaine and cannabis consumption during and after the 2019 Carnival holiday were assessed using the wastewater-based epidemiology (WBE) in the capital of Brazil, Brasília. The substances 11-nor-9-carboxy-Δ9-tetrahydrocannabinol (THC-COOH), cocaine (COC), benzoylecgonine (BE), and cocaethylene (COE) were monitored in composite samples (24 h) collected in the entrance of North-Wing (NW) and South-Wing (SW) wastewater treatment plants (WWTP) for 15 consecutive days, including the Carnival holiday. Aliquots (100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Several studies have suggested that wastewater sampling should be performed by collection proportional to the flow, which takes into account possible fluctuations in concentrations and flows over time [ 6 , 7 , 24 ]. However, this requires the use of a flowmeter to activate an automatic sampler, which limits its application [ 36 ].…”
Section: Sampling and Conditioning After Collectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have suggested that wastewater sampling should be performed by collection proportional to the flow, which takes into account possible fluctuations in concentrations and flows over time [ 6 , 7 , 24 ]. However, this requires the use of a flowmeter to activate an automatic sampler, which limits its application [ 36 ].…”
Section: Sampling and Conditioning After Collectionmentioning
confidence: 99%
“…This is especially important in situations where it is not possible to analyze the samples immediately, which requires that they be stored (sometimes for weeks) under appropriate conditions [ 15 ]. Storage of raw wastewater samples at low temperature is often used to decrease microbial degradation, with temperatures of 4 ºC [ 6 , 7 , 12 , 16 , 23 , 39 , 40 ] and especially −20 ºC [ 8 , 9 , 32 , 33 , 37 , 38 , 41 , 42 ] being most reported. This strategy can be effective in maintaining short-term stability.…”
Section: Sampling and Conditioning After Collectionmentioning
confidence: 99%
See 3 more Smart Citations